Geschichte, Ethik und Religion im Anschluß an Kant: philosophische Perspektiven "zwischen skeptischer Hoffnungslosigkeit und dogmatischem Trotz" - Langthaler, Rudolf (Deutsche Zeitschrift für Philosophie)
"Between skeptical hopelessness and dogmatic stubbornness" – Kant’s dictum succinctly and incisively suggests the critical intent underlying his philosophy of history and religion. The present volume examines Kant’s approaches toward critical thinking about history as well as the dominant countervailing interest of rationality and examines Kant’s idea of an "authentic theodicy.